Admission into primary care: are we doing enough?. Issue 2 (10th December 2013) - Preece, David; Holme, Kirsten; Frontini, Roberto; Tromp, Dick; Price, Richard
Abstract : Objectives: Research conducted by the European Association of Hospital Pharmacists (EAHP), in collaboration with the EuroPharm Forum, investigated the following: the extent to which pharmacists are in contact with each other; the opinions of pharmacists as to the extent to which continuous care is being achieved; and what are the perceived obstacles in this area. Methods: A questionnaire was circulated electronically to the respective memberships of both organisations, and was open from 5 December 2012 to 5 February 2013. Results: 534 responses were received, 400 (75%) from hospital pharmacists, 106 (20%) from community pharmacists and 28 (5%) from pharmacists working in both sectors. Most replies came from Italy (183, 34%), Denmark (78, 14%) and the UK (33, 5%). Pharmacists described communication as important or very important (hospital pharmacists (212, 53%), community pharmacists (60, 57%)) at admission. Hospital pharmacists thought that communication was either very important or important to a greater degree than community pharmacists (236, 59% vs 50, 47%) at discharge. 27% (108) of hospital pharmacists reported that they had been in contact with a community colleague 'last week'. Conversely, over half of community pharmacists replied that they had 'never' been in contact with a hospital pharmacist. Limitations: Sample size may not be representative, and the role of pharmacy technicians was not included. These results should be interpreted with caution due to the descriptive nature and lack of statistical analysis. Conclusions: Communication between the two sectors is infrequent, yet pharmacists feel it is important, especially at transitions of care. Integrated IT systems and improved remuneration systems for clinical services may improve this aspect.